Effect of different treatments on the evolution of polyamines during refrigerated storage of eggplants - Rodriguez, Silvia del Carmen (2001)
The applicability of a thermal treatment was compared with modified-atmosphere (MA) storage in relation to chilling injury (CI) and polyamines evolution in eggplants. Fruits underwent physiological disorders at 3 °C, evidenced by the appearance of surface injuries at the third day of storage, and, after moving the fruits to 20 °C, by increased respiratory activity and more intense ethylene production. Storage of fruits in sealed low-density polyethylene bags and a previous treatment with heated air (1 h at 35 °C) were both effective in retarding chilling injury, though the former was better. Two free polyamines were found in cv. Black Nite: putrescine, in greater proportion, and spermidine. Putrescine increased in control (untreated) fruits stored at 3 °C in parallel with the external appearance of chilling injury, whereas this increase was either not exhibited or retarded in treated or MA stored fruits. Spermidine did not change in control fruits at 3 °C, remaining almost constant over the whole storage period, whereas in heat- and MAP-treated fruits spermidine levels exhibited a decrease.